FLT3 inhibitor quizartinib (AC220). Issue 8 (3rd July 2019) - Naqvi, Kiran; Ravandi, Farhad
Abstract: Acute myeloid leukemia (AML) is a heterogeneous disease and remains a therapeutic challenge. Cytogenetics is a well-established prognostic factor. Recent discovery of molecular mutations has gained momentum with some being potential therapeutic targets. FLT3 mutation seen in approximately one third of the cytogenetically normal AML confers high risk of relapse and poor survival. Quizartinib is the first drug developed specifically as a FLT3 inhibitor. It has confirmed safety and efficacy in phase I and II clinical trials and has shown survival benefit over conventional chemotherapy in patients with FLT3 ITD mutated relapsed/refractory AML. Despite such promise, disease relapses are still seen. Besides the complex nature of AML itself, resistance mechanisms blunting the efficacy of quizartinib have been identified and are being investigated including TKD mutations, alternate signaling pathways and the bone marrow microenvironment. Strategies using combination of quizartinib with other TKIs/agents like crenolinib, PIM kinase, and MEK inhibitors should be further explored.